Correlation of vitamin D deficiency with frequent exacerbations in COPD patients at tertiary care hospital in western Rajasthan - Laxman Kumar Soni; Priyanka Soni; Daljeet Kaur; C. R. Choudhary; K.C. Agarwal (International Journal of Health and Clinical Research, 2022)
Background: Acute exacerbations is common in COPD patientsand has a direct corerelation with the disease severity and rising expenditure incurred on healthcare of such patients. Amongst other deficiencies in COPD Patients, deficiency of Vitamin D has always remained a topic of debate amongst the clinicians as to its role in disease exacerbations. The present study is yet another attempt to find any relation between deficiency of Vitamin D and acute exacerbation in COPD, if any. Aim of study: To assess the relationship of serum vitamin D levels with COPD severity and exacerbation. Methods: Study was conducted between September 2018 to September 2019 in which 102 patients with complaint of COPD were taken within the purview of this study and their Serum 25-hydroxyvitamin D (25-OHD) level, results of spirometry, history and records of their acute exacerbation of COPD and hospital admissions were recorded and analyzed. Results: Amongst the patients analyzed,their vitamin D status was categorized as vitamin D deficiency, vitamin D insufficiency and vitamin D sufficiency for better understanding of the results and they were found to be 15.7%, 22.5% and 61.8% respectively. A significant inverse relationship was found between deficiency of vitamin D and acute exacerbation of COPD. Conclusions: Since it was found that there is a significant inverse relation between deficiency of vitamin D and acute exacerbation of COPD, therefore it is suggested that COPD patients may be supplemented with Vitamin D so as to bring down the episodes of acute exacerbation in COPD patients.